1999
DOI: 10.1128/iai.67.3.1521-1525.1999
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Temperature and Toxicity in Murine Studies of Staphylococcal Enterotoxins and Toxic Shock Syndrome Toxin 1

Abstract: This study describes a quick (<12 h) assay for detecting temperature decreases in BALB/c and C57BL/6 mice injected intraperitoneally (i.p.) with staphylococcal enterotoxin A (SEA), SEB, or SEC3 or toxic shock syndrome toxin 1 and a potentiating dose of lipopolysaccharide (LPS). Toxin-specific antisera effectively neutralized the temperature fluctuations in this model. Orally administered SEA or SEB (50 μg/animal), with or without LPS, did not have an effect on temperature or lethality. Versus wild-type mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 40 publications
3
26
0
Order By: Relevance
“…In concordance with human data, there is a good correlation between increased serum levels of IL-1, IL-2, TNF , and/or IFN with SEA-, SEB-, or TSST-1-induced shock in mice [148][149][150][151][152][153][154][155][156][157][158][159][160]. These efforts coincide with others involving SEA and genetic knockout mice deficient in IFN or the p55 receptor for TNF [141]. In addition to potentiation of SE effects in mice by other compounds, it has been recently reported that C3H/HeJ mice (non-LPS responders) lethally respond to one or two timed doses of SEB (seven micrograms total) given intranasally [166].…”
Section: Animal Models For Ses and Tsst-1: Necessary Steps Toward A Bsupporting
confidence: 80%
See 2 more Smart Citations
“…In concordance with human data, there is a good correlation between increased serum levels of IL-1, IL-2, TNF , and/or IFN with SEA-, SEB-, or TSST-1-induced shock in mice [148][149][150][151][152][153][154][155][156][157][158][159][160]. These efforts coincide with others involving SEA and genetic knockout mice deficient in IFN or the p55 receptor for TNF [141]. In addition to potentiation of SE effects in mice by other compounds, it has been recently reported that C3H/HeJ mice (non-LPS responders) lethally respond to one or two timed doses of SEB (seven micrograms total) given intranasally [166].…”
Section: Animal Models For Ses and Tsst-1: Necessary Steps Toward A Bsupporting
confidence: 80%
“…However, incubation of a human colonic monolayer (T84 cells) with SEB and peripheral blood mononuclear cells (PBMC) increases ion flow across the cell-based barrier, thus suggesting indirect toxin effects upon gut mucosa via the immune system and released proinflam-matory cytokines [140]. A cytokine protective against various bacterial superantigens in vivo, IL-10 (but not IL-4), dose-dependently inhibits permeability of T84 cell monolayers in vitro when added before or concomitantly with SEB [135,[140][141][142].…”
Section: In Vivo Effects Of Ses and Tsst-1: A Multifactorial Eventmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] It appears that SEA is more potent than other toxin serotypes such as staphylococcal enterotoxin B (SEB) or staphylococcal enterotoxin C 1 (SEC 1 ). 13 Although LPS enhances the lethality of SEA in vivo, [13][14][15][16] the mechanism underlying the synergistic induction of pro-inflammatory cytokine responses remains unclear. In earlier studies, binding of SE to MHC class II molecules on monocytes resulted in an increase in IL-1 and TNFa.…”
Section: Introductionmentioning
confidence: 99%
“…In murine studies [41] in vivo, levels of TNF‐α increase appreciably in response to superantigen stimulation. Studies [42,43] using TNF inhibition or TNF receptor knockout mice have shown that development of clinical TSS from staphylococcal enterotoxin may be inhibited.…”
Section: Superantigensmentioning
confidence: 99%